How underappreciated autoinflammatory (innate immunity) mechanisms dominate disparate autoimmune disorders - Abacar, Kerem; Macleod, Tom; Direskeneli, Haner; McGonagle, Dennis (Frontiers in Immunology, 2024)
Historically inflammation against self was considered autoimmune which stems back to the seminal observations by Ehrlich who described serum factors, now known to be autoantibodies produced by B lineage cells that mediate “horror autotoxicus”. The 20th century elucidation of B- and T-cell adaptive immune responses cemented the understanding of the key role of adaptive immune responses in mediating pathology against self. However, Mechnikov shared the Nobel Prize for the discovery of phagocytosis, the most rudimentary aspect of innate immunity. Fast forward some 100 years and an immunogenetic understanding of innate immunity led to the categorising of innate immunopathology under the umbrella term ‘auto inflammation’ and terminology such as “horror autoinflammaticus” to highlight the schism from the classical adaptive immune understanding of autoimmunity. These concepts lead to calls for a two-tiered classification of inflammation against self, but just as innate and adaptive immunity are functionally integrated, so is immunopathology in many settings and the concept of an autoimmune to autoinflammation continuum emerged with overlaps between both. Herein we describe several historically designated disorders of adaptive immunity where innate immunity is key, including rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), systemic juvenile idiopathic arthritis (sJIA) and adult-onset Still's disease (AOSD) where the immunopathology phenotype is strongly linked to major histocompatibility complex (MHC) class II associations and responds to drugs that target T-cells. We also consider MHC-I-opathies including psoriasis and Behcet's disease(BD) that are increasingly viewed as archetype CD8 T-cell related disorders. We also briefly review the key role of barrier dysfunction in eczema and ulcerative colitis (UC) where innate tissue permeability barrier dysfunction and microbial dysbiosis contributes to prominent adaptive immune pathological mechanisms. We also highlight the emerging roles of intermediate populations of lymphocytes including gamma delta (γδ) and mucosal-associated invariant T (MAIT) cells that represent a blend of adaptive immune plasticity and innate immune rapid responders that may also determine site specific patterns of inflammation.